Comparative Analysis of Child Conversion to Islam According to Shariah Law and Malaysian Legal Framework (Kanun: Jurnal Undang-undang Malaysia, 2023)
The issue of converting children to Islam is a legal polemic that is often discussed in Malaysia. The leading cause of this problem is the action of the convert mother or father who has unilaterally converted their child under the age of 18 from the previous marriage to Islam. The parties involved frequently argue for Islamic law to support their initiatives towards Islamisation. The non-uniformity of parental consent requirements in the different provisions of Islamic law across states has also given rise to different perceptions among the community regarding the procedure for converting children to Islam. Therefore, the purpose of this paper is to study and compare the methods of converting children to Islam according to Shariah law and legal procedures in Malaysia. The literature review method was used for data collection, which was analysed using content analysis method. The results show that Shariah law has outlined several methods of converting children to Islam based on a set level of eligibility. The provisions of the law in Malaysia have set the conditions for parental consent to confirm the conversion to Islam of individuals under the age of 18.Keywords: Islamisation, children’s rights, child law, shariah law, parental consent, Malaysian legislationFull text: PDF